Anchored phylogenomics improves the resolution of evolutionary relationships in the rapid radiation of Protea L. Issue 1 (19th January 2017) - Mitchell, Nora; Lewis, Paul O.; Lemmon, Emily Moriarty; Lemmon, Alan R.; Holsinger, Kent E.
Abstract : PREMISE OF THE STUDY: Estimating phylogenetic relationships in relatively recent evolutionary radiations is challenging, especially if short branches associated with recent divergence result in multiple gene tree histories. We combine anchored enrichment next‐generation sequencing with species tree analyses to produce a robust estimate of phylogenetic relationships in the genus Protea (Proteaceae), an iconic radiation in South Africa. METHODS: We sampled multiple individuals within 59 out of 112 species of Protea and 6 outgroup species for a total of 163 individuals, and obtained sequences for 498 low‐copy, orthologous nuclear loci using anchored phylogenomics. We compare several approaches for building species trees, and explore gene tree–species tree discrepancies to determine whether poor phylogenetic resolution reflects a lack of informative sites, incomplete lineage sorting, or hybridization. KEY RESULTS: Phylogenetic estimates from species tree approaches are similar to one another and recover previously well‐supported clades within Protea, in addition to providing well‐supported phylogenetic hypotheses for previously poorly resolved intrageneric relationships. Individual gene trees are markedly different from one another and from species trees. Nonetheless, analyses indicate that differences among gene trees occur primarily concerning clades supported by short branches. CONCLUSIONS: Species tree methods using hundreds of nuclear loci provided strong support for many previously unresolved relationships in the radiation of the genus Protea . In cases where support for particular relationships remains low, these appear to arise from few informative sites and lack of information rather than strongly supported disagreement among gene trees.